The Role of Impulsiveness: Affective, Cognitive, and Financial Literacy on Financial Behavior In Generation Z Student - Kholida Arfaletha; Dian Prawitasari; Ana Kadarningsih; Vicky Oktavia (International Journal Business, Management and Innovation Review, 2025)
Generation Z refers to the population group born between 1997 and 2012. Generation Z, as digital natives, are skilled in using technology, the internet, and mobile systems, making it easy for them to shop online and increasing their tendency to be consumptive in daily activities. To reduce consumptive behavior, it is important to get used to good financial management. Of course, several factors can affect financial behavior itself. The purpose of this study is to analyze whether impulsiveness: affective and cognitive, and financial literacy, have a significant effect on the financial behavior of Generation Z students. The sampling technique is done by distributing questionnaires online through Google Forms. SEM-PLS was selected to process the data obtained. The results of this study state that affective impulsiveness doesn’t have a significant negative influence on financial behavior. Meanwhile, cognitive impulsiveness has a significantly negative impact on financial behavior in Generation Z Students.